The Routledge Hispanic studies companion to early modern Spanish literature and culture - Cacho Casal, Rodrigo; Egan, Caroline (Routledge, Taylor & Francis Group, 2022)
Early modern Spain and the end of the Golden Age / Rodrigo Cacho Casal -- The impact of Spanish imperial political culture in Iberia and Europe, 1500-1700 / Thomas James Dandelet -- Ruling the Hispanic monarchy's overseas territories / Pilar Ponce Leiva and Amorina Villarreal Brasca -- Iberian imperial rivalries and the missionary conquest of Japan / Alejandro Cañeque -- Time of catastrophe : temporalities in the transatlantic relación of Diego Portichuelo de Ribadeneyra / Elizabeth B. Davis -- Cosmography, maritime culture, and practical knowledge in the early modern Spanish Empire / Antonio Sánchez -- Juan Eusebio Nieremberg and the celestial bird : wonder and natural knowledge in early modern Spanish culture / José Ramón Marcaida -- Reading under surveillance : Arias Montano and the invention of the expurgatory index (1571) / María José Vega -- The character and cultures of credit in early modern Spanish texts : matters of trust, belief, and uncertainty / Elvira Vilches -- The classicisms of the Golden Age / Roland Béhar -- Locating Garcilaso de la Vega : between petrarchism and vernacular classicism / Antonio Gargano -- After Amaryllis began her sway : 'late' pastoral (and early fan fiction) in the poetry of Lope de Vega / Anne Holloway -- Spanish epics : visions of war and imperial ideology / Lara Vilà -- The rise and fall of romances of chivalry : 'todos ellos son una mesma cosa'? / Daniel Gutiérrez Trápaga -- The Spanish novella : CFervantes and his forerunners / Valentín Núñez Rivera -- Triangles and wheels, telescopes and flies : Gracián and the world of wit / Jeremy Robbins -- The Góngora effect : an interpretation of Gongorism / Mercedes Blanco -- The grammatical, the vernacular, and the corporeal / Caroline Egan -- From Lazarillo to 'otro Lazarillo' : the picaresque novel in Golden Age Spain / Robert A. Folger -- Don Quixote and its world : the politics of parody / Luis Gómez Canseco -- Staging Madrid : urban comedy for a new court capital / Laura R. Bass -- Exciting and exploring passions : Lope de Vega at the limits of poetics / Florence d'Artois -- The dramatic world of Pedro Calderón de la Barca : a reappraisal of his tragic works / Fausta Antonucci -- Autos sacramentales : historical world as divine pageant / Sofie Kluge -- José Antolínez, metapainting and the painting profession in Golden Age Spain / Marta Cacho Casal -- Uncovering the uncovered : nude sculptures, their display, and viewership in Hapsburg Spain / Kelley Helmstutler Di Dio -- Spanish architecture of the Golden Age : a new old story / Fernando Marías -- Daily musical life in early modern Spain / Tess Knighton -- Heavenly goods or apprenticeship in hell : framing devotion in early modern Spain / Arantza Mayo -- The Western sephardic diaspora and European literature / Valentina Nider -- 'Todos son uno' : Moriscos and the question of identity in early modern Spain / Trevor J. Dadson -- Enslaved and free Black Africans in early modern Spain / Erin Kathleen Rowe -- Lives at the margin : Spain's Gypsies and the law in the late sixteenth and early seventeenth centuries / Richard J. Pym -- Women administrators in early modern Spain / Margaret E. Boyle -- Listening to lesbians in early modern Spain / Sherry Velasco -- The transformation of masculinity / Sidney Donnell -- Desire, fear, and the inquisition : male homoeroticism in early modern Spain / Cristian Berco.
Literaturangaben
Keywords: Spain -- Civilization -- 1516-1700; Spain -- Social conditions -- To 1800; Geschichte 1500-1800; Kultur; Literatur; Spanisch